From cadaver to computer: incorporating computers into the topographical anatomy laboratory - Kim Issroff; Mark Osmond; Paul O'Higgins (Association for Learning Technology, 1997)
This paper discusses the establishment of a multimedia facility in the Topographical Anatomy Laboratory at University College London. The aims of using computers in the laboratory are to encourage self-directed learning, to provide students with a means of independent study which allows instant feedback during their learning, and to allow students to progress according to their individual requirements, while achieving the overall objectives of the curriculum.